STRATEGI PEMASARAN PADA STIE SULUT MANADO - KARIM, NUR AFNI; TAMPI, JOHNY; RUMAWAS, WEHELMINA (JURNAL ADMINISTRASI PUBLIK, 2018)
SUMMERYNorth Sulawesi Institute of Economic Sciences with various challenges both internal and externalthat can affect the continuity of this college, continuously make directional changes in order to realize theincrease in the number of students and the purpose of this college is the implementation of tridarma college,which consists of education, teaching, research and community service quality. Taking into account theinternal problems at Manado North Sulawesi High School of Economics and the external environment, StieSulut Manado needs to do strategic marketing assessment. Based on that thought, this research is done tofind the strategy formula and to determine the strategy that needs to be done, so that it can realize what isdesired by Stie Sulut Manado.The research method used is qualitative research method, where researchers collect data andprocess it into an information that will be described as a phenomenon that will be followed up in depth.Sources of data are the core respondents namely the leadership of Stie Sulut Manado with students. DataAnalysis Technique using SWOT Analysis, by compiling martrik SWOT.Based on SWOT analysis, there are things that become opportunities and strengths for Stie SulutManado which is to maintain and improve the accreditation in both study programs, management andaccounting and institutional accreditation, increase the number of educators and improve the quality oflecturers and educational staff, improve the implementation of Tridarma Perguruan high level, cooperationwith outsiders, especially excellent programs in the academic field, the addition of lecturing process in themorning, improving the quality of students by participating in various competitions both nationally andinternationally, as well as increasing the promotion of high school equivalent.Taking into account the results of research can be concluded some point that is doing aggressivestrategy by exploiting opportunity and strength maximally, continuously doing program improvement ofhuman resource quality, that is educator of lecturer and staff of education and improve student quality tocompete at national level, academic implementation to fit the established SOP.Suggestions to immediately undertake an aggressive strategy program by undertakingimprovements on all matters, especially on all strengths and opportunities in Stie Sulut Manado, need toreorganize both long-term and short-term strategic plans, and operational plans in the form of reactivitiesfor study programs and institutional accreditation , making the program of policy improvement of HumanResources both educator, education staff and student continuously, and make program of policy of controland evaluation of policy which executed in accordance with applicable provisions.Keywords: Marketing Strategy, SWOT Analysis